HUBUNGAN PERMASALAHAN KONSEP DIRI REMAJA DENGAN PEMBINAAN ORANG TUA - Meylia Sari; Al Halik (Jurnal Bimbingan Penyuluhan Islam, 2022)
Parents are the first social environment for children to interact. The results of the interaction of children with parents become the initial basis in the formation of children's behavior, especially self-concept. Adolescents who do not receive responsible guidance from their parents during their growth and development period affect the formation of an unclear self-concept that can affect their lives. For this reason, it is necessary to review the relationship between adolescent self-concept problems and parental guidance. The study used a correlational quantitative approach, with a population of 280 students while the number of samples in this study was 56 students. The instrument used in this research is a questionnaire. The findings show that 61% of adolescents experience problems with positional self-concept, with 73% of adolescents have experienced parental coaching efforts. So that there is a very strong positive relationship between self-concept problems and the coaching efforts made by parents to solve adolescent self-concept problems